Duccio Bonavia Berber - Samanez Argumedo, Roberto (2019)
The first publication of Devenir journal came to light in June 2014, almost two years after the death of Dr. Bonavia. Given the importance of his intellectual work and his work, both linked to cultural heritage, the Editorial Board considered it appropriate to pay tribute to him by disseminating his production between the new generations.